Analysis of the Influence of Land Area, Prices Received by Farmers, and Labor on Sugar Cane Production Results in Sumatra - Windi Syafitri; Izharudin Izharudin (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research aims to provide the impact of land size, income received by farmers, and number of workers on sugar cane production in five provinces in Sumatra during the 2012-2019 period. The analysis method used is panel data analysis. The time series data used covers the period 2012-2019, while the cross section data involves five provinces on the island of Sumatra, namely North Sumatra, West Sumatra, Jambi, South Sumatra and Lampung. The model applied in this research is the Fixed Effects Model (FEM). The research results show that land size and number of workers have a significant impact on sugar cane production, while the income received by farmers does not have a significant impact on sugar cane production.